Treatment of balance with Computerised Dynamic Posturography therapy in chronic hemiplegic patients - Doğaner, Işıl; Algun, Zeliha Candan (AOSIS (Pty) Ltd, 2023)
Background: As patients with hemiplegia have a high risk of falling, it is important to develop a fall rehabilitation plan and/or apply personalised treatment when necessary. Objectives: We aimed to evaluate the effects of individualised treatment with Computerised Dynamic Posturography (CDP) on balance in patients with and without a history of chronic hemiplegic falls. Method: Forty patients with hemiplegia (time post-stroke: 8–18 months) between 40 and 70 years of age in the Istanbul Yeniyüzyıl University, Gaziosmanpaşa Hospital participated in our study. The patients were divided into two groups: Group 1, falling history (n = 20) and Group 2, no falling history (n = 20). The patients in both groups were included in a traditional rehabilitation programme for 5 weeks, 5 days a week, for 1 h. The group with a history of falls also received individualised CDP treatment for 20 min, 3 days a week, for 5 weeks. Patients were evaluated with a Sensory Organisation Test (SOT) and a Berg Balance Scale (BBS). Results: In Group 1, a significant improvement was determined in the after-treatment SOT 5 values compared with the before treatment SOT 5 values (p = 0.022). Significant improvement was found in BBS (p = 0.003) and SOT 6 (p = 0.022) values in Group 2. There was no statistically significant difference in improvement between the two groups (p ? 0.05). Conclusion: Larger samples and longer duration of individualised CDP therapy studies may be required to improve balance with chronic hemiplegia and a history of falls. Clinical Implications: In addition to traditional therapy, individualised CDP treatment may be beneficial for patients with a history of post-stroke falls.
Keywords: Hemiplegia; Balance; Computerised Dynamic Posturography; Sensory Organisation Test; Chronic Hemiplegic Falls